AUTHOR’S SOCIAL IMPACT IN AMANDA GORMAN’S SELECTED POEMS - A.Irwin Irham; Dahlan, Sandra Dewi; Taufik, Muhammad (UIN Alauddin Makassar, 2024)
Social impact in this research refers to the influence of Amanda Gorman's literary works on society, especially in fighting for values such as equality, courage and solidarity. Gorman's work not only reflects her personal experiences but also has the power to inspire social change and strengthen human connections at various levels of society. This study examines how Amanda Gorman's life experiences and perspectives are expressed through her selected poems. The data were taken from the Encyclopedia Britannica, Amanda Gorman's own website, an exclusive interview with The Associated Press, Amanda Gorman's poems entitled